PENERAPAN FINITE STATE AUTOMATA PADA VENDING MACHINE SISTEM PARKIR KENDARAAN MOTOR - SUGIYANTO S.KOM.; Hamdan; Eni Heni Hermaliani; Tuti Haryanti; Windu Gata (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
The need for a parking space becomes an important thing when the area for parking does not exist or the land is getting narrower. Of course, it is necessary to think about modern and contemporary alternatives to create a comfortable parking space. The creation of a comfortable parking space using a combination of technology will be very helpful if this can be applied. The purpose of this study is to discuss the application of Finite State Automata (FSA) to vending machines for parking motorcycles. The research method is to describe Finite State Automata using Non-deterministic Finite Automata, design State Diagrams about features and interface design when the Vending Machine is implemented. The results showed that the use of Non-deterministic Finite Automata in the design of the Vending Machine parking system for motorcycles resulted in a modern, comfortable and effective future parking technology.